Non-isothermal thermo-kinetics and empirical modeling: Comparative pyrolysis of cow and Buffalo manure. (1st January 2023) - Ashraf, Muhammad; Aslam, Zaheer; Ramzan, Naveed; Anwar, Adeel; Aslam, Umair; Khan Durrani, Abdullah; Ullah Khan, Rafi; Naseer, Saad; Zeeshan Azam, Muhammad
Graphical abstract: Highlights: Thermo-kinetic parameters of Cow and Buffalo manures pyrolysis are compared. Empirical modeling by Sestak and Berggren's (SB) model is applied. The kinetic parameters for both samples are comparable. Thermodynamic parameters show a endothermic and non-spontaneous thermal degradation. Abstract: Dumping dairy manure in surroundings of confined animal feeding operations (CAFO) is an extensively implemented malpractice. This exercise poses serious environmental complications along with global warming, water, and air pollution. This study aims to explore and compare the pyrolytic conversion of the dairy manure of two common milch animals ( Cow and Buffalo ) of CAFO through detailed kinetic and thermodynamic analysis. Physicochemical characterization indicated an analogy in samples with close values of volatile contents (63 % ± 0.22), elemental carbon contents (37 % ± 0.24) and heating values (16 MJ/Kg ± 0.0.95). Subsequently, under non-isothermal and inert thermogravimetric analysis (TGA), the thermal degradations kinetics were studied through Isoconversional methods and Model fitting methods. TGA recorded major conversion (≈ 50 %) during active pyrolysis zone in temperature range of 240 to 360⁰C for both sample with similar patterns. The average activation energy (Ea) determined by the Isoconversional methods were 143.84 and 137.74 kJ mol −1, with corresponding frequency factor ( A ) values of 4.19 × 10 26 and 2.47 × 10 23 min −1 for cow manure (CM) and buffalo manure (BM), respectively. The kinetic compensation effect described strong linear relationship between the Ln(A) and Ea with comparable isokinetic temperatures. Master plot indicated that decomposition was driven by order-based reaction (Fn ) with transition to Diffusion (Dn) models. The empirical modeling by Sestak and Berggren's model showed an excellent correlation with the experimental data. Finally, thermodynamic analysis indicated a non-spontaneous and endothermic trend in entire conversion. Overall, the study suggested comparable thermo-kinetics of CM and BM pyrolysis.